Contribución proteica de animales silvestres y domésticos a los menús de los contextos rurales, peri-urbanos y urbanos de varias regiones de Colombia (2016)
The present study aims to generate information about the importance of eating bushmeat over other sources of animal protein - wild (fish), domestic or industrial- in four regions of Colombia, from the rural to the urban. The data of animal protein consumption of 1808 students in 23 rural, urban and peri-urban schools were analyzed. In urban and peri-urban areas, the most consumed animal proteins result from domestic or industrial (industrial chicken industrial egg and beef) origin, while in rural areas the fish ranks first. Bushmeat was consumed by 8 % of children in rural areas, 3 % of children in peri-urban areas and 2 % of children in urban areas. Large regional differences were observed in the Pacific region where bushmeat was most consumed. Our study shows that nutritional transition from rural to urban is characterized by the replacement of the wild protein consumption (fish and bushmeat), by domestic and industrial protein consumption, together with considerable loss of dietary diversity.